Evaluation of the gnss positioning performance under influence of the ionospheric scintillation - Caldeira, Mayara Cobacho Ortega; Caldeira, Carlos Rodrigo Tanajura; Cereja, Samara Sunny Dos Anjos; Alves, Daniele Barroca Marra [UNESP]; de Aguiar, Claudinei Rodrigues (FapUNIFESP (SciELO), 2020)
The ionosphere may not only degrade the accuracy of the GNSS positioning but also reduce its availability because there is a high dependence between signal losses and ionospheric irregularities. Irregularities in the Earth’s ionosphere may produce rapid fluctuations in phase and amplitude. These rapid fluctuations are called ionospheric scintillation. Thus, loss of signal can occur due to the effects of diffraction and refraction, which cause a weakening in the signal received by the GNSS receivers. In this way, this paper aims to evaluate the magnitude of ionospheric scintillation in Brazil and the performance of the positioning under its influence in the period of high solar activity in the current cycle (24), through the Spearman correlation analysis and the Wavelet periodogram. For that, three-year time series (2012 to 2014) of the S4 index and 3D MSE (Mean Squared Error) of three Brazilian stations with different ionospheric conditions were considered, PALM (near the Geomagnetic Equator) PRU2 (Equatorial region and Anomalies) and POAL (Mid-latitude region). Thus, it was possible to evaluate the correlation between the accuracy of the precise point positioning using only the C/A code of the GPS satellite and the S4 index. As a result, there was a correlation of 53% and 51%, using the Spearman method, for the PALM and PRU2 series, respectively. In addition, considering the analysis of space-frequency in relation to time by the Wavelet coherence method, a correlation of more than 70% is noted in the period of greatest 3D MSE concerning the spring and autumn equinox months.
Keywords: Correlation; Ionospheric Effects; S4 Index; Wavelet Coherence